TINDAK TUTUR PADA ANAK-ANAK USIA 7 TAHUN 10 BULAN: (Analisis Wacana) - Joko Santoso (AS-SALAM, 2015)
Events of speech act used by children to make requests to the partner said. Used speech acts using forms bemacam-wide in a communication event, the speakers did not always just mean to get something from the parner he said, but also to maintain good relations with partner and he said it that interaction degan running smoothly.Found a request speech acts used by childern with a wide range, which is not said directly to the target, there are 3 event with speech and speech acts reasons / argument there are three event said. Based on the author’s observations, the authors found an indirect speech act with the mode of seduction and threats.